An Iron(II)[1, 3‐bis(2′‐pyridylimino)isoindoline] Complex as a Catalyst for Substrate Oxidation with H2O2 – Evidence for a Transient Peroxidodiiron(III) Species. Issue 22 (7th June 2013) - Pap, József S.; Cranswick, Matthew A.; Balogh‐Hergovich, É.; Baráth, Gábor; Giorgi, Michel; Rohde, Gregory T.; Kaizer, József; Speier, Gábor; Que, Lawrence
Abstract: The complex [Fe(indH)(solvent)3 ](ClO4 )2 (1 ) has been isolated from the reaction of equimolar amounts of 1, 3‐bis(2′‐pyridylimino)isoindoline (indH) and Fe(ClO4 )2 in acetonitrile and characterized by X‐ray crystallography and several spectroscopic techniques. It is a suitable catalyst for the oxidation of thioanisoles and benzyl alcohols with H2 O2 as the oxidant. Hammett correlations and kinetic isotope effect experiments support the involvement of an electrophilic metal‐based oxidant. A metastable green species (2 ) is observed when1 is reacted with H2 O2 at –40 °C and has a Fe III (μ‐O)(μ‐O2 )Fe III core on the basis of UV/Vis, electron paramagnetic resonance, resonance Raman, and X‐ray absorption spectroscopic data. Abstract : A monoiron(II) complex of 1, 3‐bis(2′‐pyridylimino)isoindoline reacts with H2 O2 to form a green diiron(III) peroxido intermediate, which may serve as the precursor to the active oxidant in thioanisole and benzyl alcohol oxidation.